WHAT SPARKS RURAL INTENTION TO USE MOBILE BANKING SERVICES? - Tiwa, Angel Syerina; Kindangen, Paulus; Wangke, Shinta (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
In recent years, financial inclusion has gained attention for its role in driving economic growth, social equality and financial system stability. As digital technologies evolve, expanding access to financial services, especially in rural areas, has become essential for reducing poverty and bridging socio-economic gaps. This study explores how mobile banking advances financial inclusion, focusing on factors that influence adoption in rural areas. Using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, the research employs a quantitative approach, utilizing structured questionnaires to gather data from 50 respondents who hold Bank Rakyat Indonesia (BRI) accounts in Motoling Village. The results reveal that when considered simultaneously, Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions all significantly influence the intention to use BRI mobile banking (BRImo). Effort Expectancy and Social Influence have a positive and significant impact on the intention to use BRImo. While Performance Expectancy and Facilitating Conditions do not have a significant impact individually, they still exhibit a positive effect on adoption intentions. This highlights the complex, interconnected factors that influence mobile banking adoption in rural areas.   Keyword: Financial Inclusion, Mobile Banking, UTAUT, Intention to Use